(untitled) (Global Journal of Human-Social Science, 2012)
The profiles and determinants of child poverty in rural Nigeria were identified using the Demographic and Health Survey 2008 data The multidimensional child poverty concept was applied to children under-5 years of age In all a total of 4 543 children were analyzed About half of the children were male and the mean age for all the children is 29 months old A single step Multiple Correspondence Analysis MCA was carried out to generate weights for five dimensions used in the multidimensional poverty estimations These dimensions are safe drinking water sanitation housing health and nutrition The Alkire and Foster 2007 counting approach was applied to generate multidimensional poverty profiles for the children When the poverty cut off K 1 52 of the children were multidimensional poor as against 27 9 poor when k 3 This implies that when children are deprived in at least one dimension 52 are multidimensional poor The health and sanitation dimensions had the highest relative contribution of 38 54 and 22 58 respectively to the overall multidimensional poverty index